Seasonality in Local Food Markets and Consumption : Evidence from Tanzania - Kaminski, Jonathan; Christiaensen, Luc; Gilbert, Christopher L. (World Bank, Washington, DC, 2016)
This paper revisits the extent of seasonality in African livelihoods. It uses 19 years of monthly food prices from 20 markets and three years of nationally representative household panel surveys from Tanzania. Trigonometric specifications are introduced to measure the seasonal gap. When samples are short and seasonality is poorly defined, they produce less upward bias than the common dummy variable approach. On average, the seasonal gap for maize prices is estimated to be 27 percent; it is 15 percent for rice. In both cases it is two and a half to three times higher than in the international reference market. Food price seasonality is not a major contributor to food price volatility, but it does translate into seasonal variation in caloric intake of about 10 percent among poor urban households and rural net food sellers. Rural net food-buying households appear able to smooth their consumption. The disappearance of seasonality from Africas development debate seems premature.